2018
DOI: 10.3892/or.2018.6639
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment model constructed by differentially expressed lncRNAs for the prognosis of glioma

Abstract: A risk assessment model was constructed using differentially expressed long non-coding (lnc)RNAs for the prognosis of glioma. Transcriptome sequencing of the lncRNAs and mRNAs from glioma samples were obtained from the TCGA database. The samples were divided into bad and good prognosis groups based on survival time, then differently expressed lncRNAs between these two groups were screened using DEseq and edgeR packages. Multivariate Cox regression analysis was performed to establish a risk assessment system ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…All three high-quality models exhibit high accuracy [ 71 73 ]. Except for the slightly decreased AUC values (0.722) when submitted to external validation based on Chen's study [ 73 ], the other two models show similar high accuracy in training, internal validation, and the entire set with AUC from 0.84 to 0.91 [ 71 , 72 ].…”
Section: Rna Modelsmentioning
confidence: 99%
“…All three high-quality models exhibit high accuracy [ 71 73 ]. Except for the slightly decreased AUC values (0.722) when submitted to external validation based on Chen's study [ 73 ], the other two models show similar high accuracy in training, internal validation, and the entire set with AUC from 0.84 to 0.91 [ 71 , 72 ].…”
Section: Rna Modelsmentioning
confidence: 99%
“…S. Wu et al, 2017). Some lncRNAs have been known to be abnormally expressed in glioma tissues and take part in the progress of glioma (Q. N. Chen et al, 2017;C. Hu, Zhou, Liu, & Kang, 2018;D.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, lncRNAs have attracted increasing attention owing to their regulatory roles in the progress of cancers (Song, Zhang, Huang, & Hai, 2018; X. S. Wu et al, 2017). Some lncRNAs have been known to be abnormally expressed in glioma tissues and take part in the progress of glioma (Q. N. Chen et al, 2017; C. Hu, Zhou, Liu, & Kang, 2018; D. M. Wu et al, 2018). In this study, we concentrated on the function of HNF1A‐AS1, and found that HNF1A‐AS1 was upregulated in glioma tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the time has come to abandon the old binary risk stratification (“low-risk” versus “high-risk”), which still contains arbitrary elements (like the age cut-off), proving impractical in real-world clinical decision-making, and to adopt a new one, also taking into account many emerging prognostic biomarkers (BRAF V600E mutation, methylome, transcriptome sequencing) ( 17 ).…”
Section: Opinionmentioning
confidence: 99%